2022
DOI: 10.21037/tlcr-22-207
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluating the need for mediastinal lymph node dissection and exploring lncRNAs as biomarkers of N2 metastasis in T1 lung adenocarcinoma

Abstract: Background: Although a well-acknowledged component of curative surgery for lung cancer, investigators have recently questioned the need for mediastinal lymph node dissection (MLND) in early-stage lung cancer cases. As such, the accurate prediction of N2 stage prior to surgery has become increasingly critical. But diagnostic biomarkers predicting N2 metastases are deficient, which are urgently needed.Methods: We extracted the data of non-small cell lung cancer (NSCLC) patients whose clinical information and fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
(23 reference statements)
0
9
0
1
Order By: Relevance
“…The aberrant upregulation of MIR4435-2HG in LUAD can upregulate related transcription factors and promote the EMT process 49 . LINC00892 has the potential as a biomarker of metastasis in T1 LUAD 50 . LINC00460 is upregulated in the LUAD group and played an important role in the control of oncogenes and tumor suppressors 51 .…”
Section: Discussionmentioning
confidence: 99%
“…The aberrant upregulation of MIR4435-2HG in LUAD can upregulate related transcription factors and promote the EMT process 49 . LINC00892 has the potential as a biomarker of metastasis in T1 LUAD 50 . LINC00460 is upregulated in the LUAD group and played an important role in the control of oncogenes and tumor suppressors 51 .…”
Section: Discussionmentioning
confidence: 99%
“… 14 Hao and colleagues found that five lncRNAs ( SCAMP1‐AS1 , LINC00892 , LINC01481 , and AC004812.2 , AC099522.2 ) could be potentially used as diagnostic biological markers for screening N2 metastasis in pT1 lung adenocarcinoma (LUAD). 15 Elevated expression levels of lncRNA LCIIAR foreseen a poor prognosis in lung cancer. 16 Tumor‐suppressing lncRNAs are also reported.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA MARCKSL1‐2 was remarkably downregulated in docetaxel (DTX)‐resistant lung adenocarcinoma cells, while overexpression of this lncRNA in tumor cells reversed DTX resistance 14 . Hao and colleagues found that five lncRNAs ( SCAMP1‐AS1 , LINC00892 , LINC01481 , and AC004812.2 , AC099522.2 ) could be potentially used as diagnostic biological markers for screening N2 metastasis in pT1 lung adenocarcinoma (LUAD) 15 . Elevated expression levels of lncRNA LCIIAR foreseen a poor prognosis in lung cancer 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the leading cause of cancer-related death worldwide. Non-small cell lung cancer (NSCLC) accounts for 85% of all lung cancers, with more than half manifesting histologically as lung adenocarcinoma (LUAD) ( 1 , 2 ). Prognostic factors for LUAD are essential for developing prognostic assessments that might potentially identify patients who will benefit most from aggressive treatment choices while protecting others from the toxicity ( 3 ).…”
Section: Introductionmentioning
confidence: 99%